BIOMECHANICAL BEHAVIOR OF ENDOSONICS (ETIMA, 2024)
Endosonics is used for root canal instrumentation and disinfection. An endosonics insert is designed to shaping and allow the traditional endodontic irrigant, sodium hypochlorite, to pass through and along the endo-sonic files. The irrigant is activated by the ultrasonic energy imparted from the energized instruments and the root canal becomes an ultrasonic bath. The ultrasonic tip vibrates at a high frequency and produces acoustic streaming and cavitation, which helps to dislodge and remove the organic and inorganic part of the smear layer and gram+ and gram – bacteria from endodontic system. This review of the literature aims at presenting the biomechanical work of endosonic in endo cavity and its clinical applications in a modern-day endodontic practice.The following electronic databases were searched: Pubmed, Web of Sciences, Embase, Medscape, Web of Science and Cochrane Library. This study is based on review on published articles written in English language, reporting results related to biomechanical work of endosonics. The articles are full reading text, with no publication date restriction. After implementation of inclusion and exclusion criteria, from the total 104 articles, 82 articles were discarded and only 22 articles were taken for detailed analysis. A number of researchers have shown that ultrasonically assisted irrigation improves the cleaning efficiency in root canal treatments. In the study of Joyce et al., specially made endosonic dies and diamond instruments are energized by means of a Cavitron ultrasound generator (above 20 kHz frequency). Piezoelectric units have some advantages compared with earlier magnetostrictive units because they offer more cycles per second, 40 versus 24 kHz.In summary, endosonics is a valuable tool in the field of endodontics, as it helps to improve the effectiveness of root canal treatment while reducing the need for invasive procedures. The use of endosonics in endodontics provides several benefits, including improved cleaning and shaping of the root canal system, reduced treatment time and improved treatment outcomes. Additionally, endosonics is minimally invasive and can help preserve more of the natural tooth structure, reducing the need for more extensive dental procedure. As well as explaining the endosonics biomechanical work, the work provides a basis for the further development and optimisation of the design of endosonic files.
Keywords: endodontics; ultrasonics; endosonics